Accounting Information Technology and its Role in Raising the Level of Professional Performance of Internal Auditing - Mahdi, Muslim Hamid; Mahdi, Zainab Zuhair; Sweih, Gabbar Hassan (American Journal of Economics and Business Management, 2024)
This research aims to know the role of information technology in improving the performance of internal auditing, by highlighting the obstacles facing the use of information technology during internal auditing and understanding the extent of the internal auditor's awareness, Due to the importance that provides in improving audit services and explaining its role in providing accurate results and large information with high efficiency, in addition to the impact of information technology in reducing internal audit risks as a result of the large size of economic units and the diversity of their legal forms due to the great development occurring in all economic sectors. This led to the need for the internal auditor to provide services with the highest quality, one of the most important results that were reached is that information technology works to improve auditing procedures and reducing the risk by monitoring the computer performance daily with operational activities and confidentiality of information and the inability to access important information for unauthorized persons. Among the most important recommendations is the necessity for internal auditors to be Awareness of the importance of this technology when performing auditing services and reducing the risk when monitoring computer performance daily with operational activities, the confidentiality of information, and the inability to access important information except for authorized persons. The research concluded that the hypotheses are correct.